2021
DOI: 10.19027/jai.20.2.115-129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corn steep powder as a protein source for feed of Nile tilapia Oreochromis niloticus

Abstract: This study was aimed to evaluate the use of corn steep powder (CSP) as a plant protein source in Oreochromis niloticus diet. A commercial feed with 28% protein content and 368 kcal/g energy was used as reference diet, while the test feed consisting of various CSP content, namely 0%, 10%, 20%, and 30% and feed containing soybean meal (SBM) at the level of 20% and 30%. Tilapia were used in the trial with the initial body weight of 6.44 ± 0.29 g, and reared for thirty days in the aquarium at the density of fiftee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…One of the nutritional aspects that are specifically important to be in the feed ingredient and directly determine the cost is protein 9 . For the cost, a relatively low price is still on the top of the list and sustainability is needed to be maintained 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the nutritional aspects that are specifically important to be in the feed ingredient and directly determine the cost is protein 9 . For the cost, a relatively low price is still on the top of the list and sustainability is needed to be maintained 30 .…”
Section: Resultsmentioning
confidence: 99%
“…The high-quality feed can be fulfilled through ingredients selection with balanced nutritional content. Protein is one of the nutritional aspects that are especially important to have in the feed ingredient because it directly affects the cost 9 . The optimal dietary protein level promotes the efficiency of aquaculture and reduces feed costs 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The lowest food conversion ratios recorded in diets T3 and T1 indicate that fish fed with these two diets effectively converted their food to body growth than those fed with diet T4 which had the highest food conversion ratio (Fry et al 2018). The lowest food conversion ratios recorded in diets T3 and T1 could be likened to low crude fibre, elevated crude protein, and low levels of antinutritional elements which promote or support food digestibility (Hermawan et al 2021). Diet T4 with 30% inclusion levels of Leucaena leaf meal which recorded the highest food conversion ratio, could be attributed to high fibre contents in the diet due to high inclusion level of plant protein (Leucaena leaf meal), low crude protein and high levels of nutrient-inhibitory elements like saponin and mimosine leading to poor digestibility and palatability (Agbo et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Wu et al [21] reported that CGM could replace 75% of dietary FM (equal to 16.2% of CGM inclusion level in diet) without reducing the growth performance of abalone (Haliotis discus hannai) significantly. Besides, Hermawan et al [22] reported that CGM could be incorporated into the Nile tilapia feed diet.The economic evaluation indicated that incorporating CGM into fish feed might lower feeding costs by 5-6 times compared to FM-based diets.…”
Section: Introductionmentioning
confidence: 99%